2020
DOI: 10.21203/rs.3.rs-16202/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurological outcome after extracorporeal cardiopulmonary resuscitation for in-hospital cardiac arrest: a systematic review and meta-analysis

Abstract: Background: In hospital cardiac arrest (IHCA) is a major adverse event with a high mortality rate if not treated appropriately. Extracorporeal cardiopulmonary resuscitation (ECPR), as adjunct to conventional cardiopulmonary resuscitation (CCPR) is a promising technique for IHCA treatment. Evidence pertaining to neurological outcomes after ECPR is still scarce. Methods: We performed a comprehensive systematic search of all studies up to December 20th 2019. Our primary outcome was neurological outcome after ECPR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…4 Survival after CA is most meaningful when accompanied by favorable neurologic outcome, with a reported rate of 25.2% in a systematic review. 8 The overall 18.6% 3-month favorable neurologic outcome in our cohort was comparable and showed that territory-wide pilot programs could be successful after reorganization of hospital resuscitation procedures – with early involvement of the mobile ECMO team and cardiology support for emergency coronary revascularization when appropriate.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…4 Survival after CA is most meaningful when accompanied by favorable neurologic outcome, with a reported rate of 25.2% in a systematic review. 8 The overall 18.6% 3-month favorable neurologic outcome in our cohort was comparable and showed that territory-wide pilot programs could be successful after reorganization of hospital resuscitation procedures – with early involvement of the mobile ECMO team and cardiology support for emergency coronary revascularization when appropriate.…”
Section: Discussionsupporting
confidence: 61%
“…The nECPR score, which was developed to predict neurologic outcomes, performed better than the ECPR score in predicting favorable 3-month neurologic outcomes (nECPR score -median [IQR], 14.1 [9.9-23] vs. 22. 1 [18.6-29.8]; P = 0.002; AUROC, 0.73; 95% CI, 0.61 to 0.86; ECPR score -median [IQR], 10 [10][11][12] vs. 9 [7][8][9][10]; P = 0.002; AUROC, 0.72; 95% CI, 0.59 to 0.85). We showed that incorporating APACHE IV scores to the nECPR score further increased the performance of the model (AUROC, 0.80; 95% CI, 0.70 to 0.90) (see Figure 2b).…”
Section: Validation Of Existing Risk Scoresmentioning
confidence: 99%
“…Although their patients undergoing extracorporeal membrane oxygenation were twice as many as ours, our subjects had a better prognosis regardless of the selection bias of opting for patients with better conditions in ECMO therapy. 28 Second, our relatively small sample size potentially interferes with the power of the results. Furthermore, in their study, good neurological status was substantial (17.0% among all patients with IHCA) at the 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Extracorporeal cardiopulmonary resuscitation (ECPR), achieved via the use of veno-arterial extracorporeal membrane oxygenation (ECMO) in conjunct with CCPR, is a promising technique that supports a subgroup of critically ill OHCA patients by providing increased perfusion. [6][7][8] However, ECPR is a complex intervention that requires a highly trained team, specialized equipment, and multidisciplinary support within a healthcare system. 9 This highly invasive therapy is costly to implement, has a setup time ranging between 15 and 30 minutes and the procedure itself can cause life-threatening complications to the patient.…”
Section: Introductionmentioning
confidence: 99%